Synthesis and Characterization of Nano Zinc Oxide by Sol Gel Spin Coating - and P. Raji2, K. Balachandra Kumar1 (Recent Research in Science and Technology, 2011)
ZnO thin film has been deposited onto FTO glass substrate by the sol-gel spin coating method. Zinc acetate dehydrate, 2-methoxyethanol and monoethanolamine are used as a starting material, solvent and stabilizer, respectively. Dropping the coating solution into FTO substrate rotated at 3000 rpm for 20 sec using a spin coater. After the spin coating process the film is allowed to dry at 300o C for 10 min in a furnace to evaporate the solvent and to remove organic residuals. The XRD and SEM measurements confirmed that the thin films grown by sol-gel technique have good crystalline hexagonal wurtzite structure and homogenous surfaces. The optical absorbance of the deposited films is characterized by UV-VIS-NIR spectrometry. The optical band gap of deposited films is found to be 3.44 eV. The photoluminescence, FTIR and Raman spectra were studied and reported.